Integration of biofuel-induced electricity generators (BEGs) with wearable biosensing devices - Zaghum Abbas S.; Beddu S.; Liyana Mohd Kamal N.; Anwar N.; Mohamad D.; Binti Rahman N.; Binti Baharudin S. (Elsevier Ltd, 2025)
This review article explores the potential revolutionary uses of biofuel-induced electricity generators (BEGs) integrated into portable biosensing devices. It describes the workings, and benefits of BEGs-based biosensors while highlighting the complementary nature of energy production and biosensing. The article delves into the ways BEGs transform biosensing capabilities in wearable technology, highlighting their ability to sustain themselves, compatibility with living organisms, and ongoing power production. BEGs eliminate the need for external power sources by enabling independent and uninterrupted operation through the metabolic activity of microorganisms. Their compatibility with the human body guarantees a secure and pleasant on-body experience. Wearables that incorporate BEGs allow for the continuous tracking of ambient variables, physiological data, and biomarkers. The review highlights the exciting possibilities of BEGs based-biosensors in healthcare, environmental monitoring, and other fields, paving the way for autonomous, continuous monitoring in the future to enhance health management and raise environmental consciousness. ? 2024 Elsevier Ltd